Space and Pluralism : Can Contemporary Cities Be Places of Tolerance? - Moroni, Stefano, 1965- (Book collections on Project MUSE., 2016)
This book addresses the social, functional and symbolic dimensions of urban space in today's world. The twelve essays are grouped in three parts, ranging from a conceptual framework to case descriptions rich with illustrations. They provide a valuable service in exploring the nature and significance of social space and particular aspects of its contemporary distribution and contestation. The book addresses a topic that is intrinsically interdisciplinary. Questions of space are examined from a rich variety of disciplinary perspectives in a welcome range from urban planning to political philosop.